A major, intraplate, normal‐faulting earthquake: The 1739 Yinchuan event in northern China. Issue 1 (5th January 2016) - Middleton, Timothy A.; Walker, Richard T.; Parsons, Barry; Lei, Qiyun; Zhou, Yu; Ren, Zhikun
Abstract: A large continental normal‐faulting earthquake occurred in the Yinchuan Graben in northern China on 3 January 1739. This event is of significant interest for two reasons. First, it has been suggested on the basis of historical records of shaking that this was a magnitude 8.0 event. If this is true, the 1739 earthquake would be one of the largest continental normal‐faulting earthquakes ever recorded, and this should prompt us to consider the factors contributing to its unusual size. Second, there has been some debate in the literature about the causative structure, with at least three different faults posited as the seismogenic source. We use five 14 C ages to date a series of scarps on the East Helanshan Fault, which lies to the west of the graben, and bracket the scarp formation to the last 350 years. We use high‐resolution, stereo imagery from the Pleiades satellites to build a 1 to 2 m resolution DEM of the fault and combine this with field observations to map the East Helanshan rupture in detail. We then construct a throw distribution, determine the slip vector azimuth, and reassess the earthquake magnitude using simple scaling relationships. We conclude that the 1739 earthquake occurred on the East Helanshan Fault, had a rupture length of approximately 87 km, a maximum throw of 5.1 m, and an average throw of 3.0 m, yielding a best estimate magnitude in the range M w  7.1 to M w  7.6. We suggest that the previous magnitude estimates are biased by enhanced shaking of the sediments within the Yinchuan Graben. Key Points: The 1739 Yinchuan earthquake occurred on the East Helanshan Fault The earthquake had a magnitude in the range 7.1 to 7.6 Valuable to combine historical earthquake accounts with geological observations